The Economic Effects of Human Rights - Lorenz Blume; Stefan Voigt (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2004)
Economists are often skeptical concerning the economic effects of various forms of human rights: it has been argued that basic human rights can make the legal system less efficient but also that extensive social rights are incompatible with market economies. It is argued here that basic human rights are a precondition for other kinds of rights such as property and civil rights and that they are thus efficiency-enhancing. Four different groups of rights are identified. It is asked what effects they have on welfare and growth. The transmission channels through which the different rights affect welfare and growth are identified by estimating their effects on investment in both physical and human capital and overall productivity. Basic human rights have indeed a positive effect on investment, but do not seem to contribute to productivity. Social or emancipatory rights, in turn, are not conducive to investment in physical capital but do contribute to productivity improvements. None of the four groups of rights ever has a significant negative effect on any of the economic variables here included.
Keywords: P14; O57; H41; K10; H73; O11; P51; 330; Grundrecht; Menschenrechte; Sozialrecht; Investition; Bildungsinvestition; Wirtschaftswachstum; Schätzung; Wohlfahrtseffekt; Welt